Modeling risky asset prices with jump-diffusion processes - Jiang, Meiling (2008)
Modeling the prices of Risky Assets using a Jump-Diffusion process and comparing its effectiveness to the traditional Pure Diffusion models through the likelihood ratio test. The EM method has been employed in finding parameters estimates of the Jump-Diffusion model.